Covalent Organic Frameworks: Sulfur‐ and Nitrogen‐Rich Porous π‐Conjugated COFs as Stable Electrode Materials for Electro‐Ionic Soft Actuators (Adv. Funct. Mater. 46/2020). (12th November 2020) - Mahato, Manmatha; Tabassian, Rassoul; Nguyen, Van Hiep; Oh, Saewoong; Nam, Sanghee; Kim, Kwang Jin; Oh, Il‐Kwon
Abstract : In article number 2003863, Il‐Kwon Oh and co‐workers design and synthesize porous π‐conjugated covalent organic frameworks as active electrode materials for electro‐ionic artificial muscles. These artificial muscles show fast rise times, short phase delays, strong blocking force, high bending displacement, and ultralong durability, and can be applied to soft touch robotics for opening folders and swiping pages on fragile displays.